Mubadalah as a Pillar of Family Resilience in Indonesia in Facing the Challenges of Information Disruption - Fathul Muin; Farah Batrisyia Binti Mohd Ridzwan; Susi Nurkholidah; Diah Mukminatul Hasyimi; Sakirman (Brajamusti Publication, 2025)
This article is about the concept of mubadalah as a pillar of family resilience in Indonesia in facing the challenges of the era of information disruption. Family life in the era of information disruption faces major challenges, especially husband and wife relations. The purpose of this article is to analyze mubadalah as a pillar of household resilience in Indonesia amidst information disruption. This research method uses kualitative, data sources are obtained from library materials. The data analysis uses the theory of mutuality or mubadalah. The results of the study found that the era of information disruption has given rise to challenges for family life such as misinformation, decreased quality of interpersonal communication, technology addiction which has an impact on family disharmony. The concept of mubadalah has significant relevance in strengthening family resilience in Indonesia in facing these challenges. Mubadalah offers a holistic approach to maintaining family harmony and stability. The principle of mubadalah, which emphasizes justice, equality, and cooperation between family members, can be the main pillar in building relationships that are mutually supportive, respectful, and solution-oriented. Mubadalah is not only relevant as a religious concept, however also as a practical solution in responding to the increasingly complex social dynamics in the modern era.